ATH-01 The OVESCO over the scope clip (OTSC) reduces gastrointestinal haemorrhage re-bleeding rates–first UK series. Issue 2 (June 2019) - Keen, Timothy; Ochieng, Alvin; Boger, Philip; Hollingworth, Thomas; Patel, Praful; Rahman, Imdadur
Abstract : Introduction: The OVESCO over the scope clip (OTSC) has recently been described in treating upper gastrointestinal (UGI) haemorrhage in Europe. The aim of this study was to determine whether use of the OTSC was associated with lower UGI haemorrhage re-bleeding rates and mortality in the UK. Methods: Consecutive episodes of UGI haemorrhage treated with the OTSC were identified from a prospective database in a UK tertiary centre over a 2-year period. Treatment with OTSC was opted for patients with high risk features or failed conventional therapy. Over the same time period, patients within the same centre with UGI haemorrhage treated with standard endoscopic therapy were retrospectively identified as a control group. Patient demographics, 7 day re-bleeding rate, 30 day re-bleeding rate and 30 day mortality rates were compared from each group. T-test and Pearson's Chi-square test were used as appropriate. Results: 408 episodes of UGI haemorrhage were identified requiring endoscopic intervention. Of these 59 high risk lesions were treated with the OTSC; forest 1a-20%, 1b-31%, 2a-29%, 2b-20%. The sites of lesions treated with the OTSC included oesophagus (10%), stomach (20%) and duodenum (70%). Pathology included 48 (81%) ulcers, 4 (6.8%) Mallory-Weiss tears, 3 (5%) Dieulafoy, 2 (3.4%) post-angiographic coil ulcer, 1 (1.7%) post-EMR and 1 (1.7%) anastomotic bleed. 349 episodes were identified for the control group. Median age was 70 years in the OTSC group versus 72 years in the control group (p=0.21). There was no significance difference in sex between the OTSC group and the control group (64% male vs 70% male, p=0.41). Compared to the control group, the OTSC group had lower 7-day re-bleeding rate (12% vs 3.4%, p=0.048) and a trend towards lower 30-day re-bleeding rate (15% vs 6.8%, p=0.10). Although all-cause mortality in OTSC group was similar to the control group (6.8% vs 8.3%, p=0.70); there was a trend to lower UGI haemorrhage mortality in the OTSC group (0% vs 4.7%, p=0.09). Conclusions: This is the first UK series to demonstrate that use of the OTSC for episodes of UGI haemorrhage requiring endoscopic therapy is associated with statistically significant lower rates of re-bleeding at 7 days. There is a trend towards reduced 30 day re-bleeding and UGI haemorrhage related mortality. Further studies are urgently required to assess whether this trend is statistically significant and to assess this exciting new modality for a condition where UK mortality has not been reduced for many years.